Preparation method of multifunctional medical titanium alloy with bone-like structure

By changing the powder particle size and pore-forming agent addition, combined with discharge plasma sintering technology, a multi-functional medical titanium alloy for bone-like structure was prepared, which solved the problems of titanium alloy implants in bone tissue integration capabilities and bacterial infection, and achieved efficient bone integration and antibacterial effects.

CN119506657APending Publication Date: 2025-02-25KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693792.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing titanium alloy implants have problems with poor bone tissue integration capabilities, mismatch of elastic modulus, bacterial infection, etc., resulting in loosening and breaking of the implanted site and requiring frequent revision or re-implantation.

Method used

By changing the powder particle size and pore-forming agent addition amount, a multifunctional medical titanium alloy for bone-like structures with different porosity and pore sizes was prepared. Combined with discharge plasma sintering technology, a titanium alloy with outer porous layer, inner core porous layer and intermediate dense layer was prepared.

Benefits of technology

High compressive strength and low elastic modulus are achieved, which promotes bone tissue growth and nutrient delivery, reduces bacterial infection, and improves the bone integration effect of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a multifunctional medical titanium alloy with a bone-like structure, and belongs to the field of biomedical materials. The preparation method is characterized by comprising the following steps: 1) taking pre-alloyed Ti6Al4V5Cu and Ti6Al4V powder as raw materials; 2) mixing the Ti6Al4V powder with an NH4HCO3 pore forming agent to obtain a mixture I; 3) mixing the Ti6Al4V5Cu powder with paraffin to obtain a mixture II; (4) mixing the Ti6Al4V5Cu powder with an NH4HCO3 pore forming agent to obtain a mixture III; 5) sequentially filling the mixture I, the mixture II and the mixture III into a stainless steel mold, and performing compression molding; 6) performing thermal degreasing in a tubular furnace; 7, the degreased green body is placed into a graphite mold, the graphite mold is placed into a discharge plasma sintering furnace to be sintered, and the multifunctional medical titanium alloy of the bone-like structure is obtained.The multifunctional medical titanium alloy of the bone-like structure prepared through the method can improve the osseointegration effect of an implant, can effectively inhibit bacterial infection after implantation and has application prospects in the aspect of orthopedic implants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a bone-like structure multifunctional medical titanium alloy, belonging to the preparation technology in the field of biomedical materials. Background Art

[0002] In recent years, the number of patients with diseases such as human hard tissue lesions, trauma and injuries has increased year by year. The clinical demand for biomedical artificial substitutes or implant materials and products for repairing and reconstructing different lesions and damaged parts in the human body has shown a substantial growth trend. Among the current artificial substitutes or implants for hard tissues (such as artificial hip / knee / shoulder joints, bone trauma products, dental implants, etc.), titanium alloys represented by Ti6Al4V have been widely used in clinical practice due to their excellent mechanical properties, good wear and corrosion resistance, and biocompatibility. However, after long-term implantation, it is still found that there are phenomena such as poor integration between implants and bone tissues, mismatch of elastic modulus, loosening and fracture of prostheses caused by bacterial infection at the implant site, etc. These patients need to be renovated or re-implanted later, which causes great pain and economic burden to patients. Summary of the invention

[0003] In order to overcome the shortcomings of the existing technology, the present invention proposes a method for preparing a multifunctional medical titanium alloy with a bone-like structure, aiming at the problems of poor bone tissue integration, elastic modulus mismatch, bacterial infection, etc. of the current titanium alloy implants. The purpose of creating different porosities and pore sizes is achieved by changing the powder particle size and the amount of pore-forming agent added. At the same time, antibacterial titanium alloy powder raw materials are selected, and the spark plasma sintering technology is used to prepare a multifunctional medical titanium alloy with a bone-like structure that meets different needs.

[0004] In order to achieve the above object, the present invention provides a method for preparing a bone-like structure multifunctional medical titanium alloy, comprising the following steps:

[0005] (1) Pre-alloyed spherical Ti6Al4V5Cu alloy powder with a particle size of 10 to 20 μm and angular Ti6Al4V alloy powder with a particle size of 40 to 50 μm are used as raw materials;

[0006] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them to obtain a mixture I for standby use, wherein the mass fraction of the NH4HCO3 powder is 30-40%;

[0007] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 30-40° C., cooling them to room temperature, and obtaining a mixture II for standby use; wherein the addition amount of Ti6Al4V5Cu and the liquid paraffin is 4.86-5.67 g / ml;

[0008] (4) adding the Ti6Al4V5Cu metal powder used as the core porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 45-60%;

[0009] (5) Vaseline is evenly coated on the inner wall of the stainless steel mold, and then the mixture I of step (2) is first filled into the stainless steel mold to be pressed into a hollow cylinder, and then the mixture II of step (3) is filled between the cylinder and the core, and finally the mixture III of step (4) is filled into the core of the cylinder; and the mixture is hammered and compacted while being filled;

[0010] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 40 to 60 kN at a speed of 1 to 3 kN / s, maintaining the pressure for 20 to 40 minutes, and removing the mold to obtain a green billet;

[0011] (7) placing the green body of step (6) into a tubular furnace, degreasing the green body in a furnace with a vacuum degree of 10 to 25 Pa and continuously introducing an argon atmosphere with a purity of 99.99%. During the degreasing process, the temperature is raised to 230 to 250° C. at a heating rate of 5° C. / min, then kept at this temperature for 220 to 240 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a degreased green body for standby use;

[0012] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 4 to 6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 90 to 100°C / min, and then increased to 900°C at a heating rate of 100 to 110°C / min, and then increased to 1100 to 1200°C at a heating rate of 45 to 50°C / min, and kept warm for 5 to 10 minutes. Thereafter, under the condition of a vacuum degree of 4 to 6 Pa in the furnace, the temperature is cooled to 150 to 250°C at a cooling rate of 70 to 90°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0013] Preferably, the chemical composition of the Ti6Al4V5Cu metal powder in step (1) is: Al: 5.50-6.50wt.%, V: 3.50-4.50wt.%, Cu: 4.5-6.0wt.%, Fe: ≤0.25wt.%, C: ≤0.08wt.%, N: ≤0.03wt.%, H: ≤0.008wt.%, O: ≤0.13wt.%, and the balance is Ti.

[0014] The chemical composition of Ti6Al4V metal powder is: Al: 5.50~6.75wt.%, V: 3.50~4.50wt.%, Fe: ≤0.30wt.%, C: ≤0.08wt.%, N: ≤0.05wt.%, H: ≤0.015wt.%, O: ≤0.20wt.%, and the balance is Ti.

[0015] Preferably, the Ti6Al4V5Cu metal powder in step (1) is prepared by electrode induction melting and inert gas atomization method; and the Ti6Al4V metal powder is prepared by ball milling.

[0016] Preferably, the purity of the NH4HCO3 powder in steps (2) and (4) is analytical purity and the particle size is 300 to 500 μm.

[0017] Preferably, the stainless steel mold in step (5) includes a fixed sleeve, a cushion block arranged at the bottom of the fixed sleeve shaft hole, an inner movable sleeve movably arranged on the cushion block, a core rod movably arranged in the inner movable sleeve shaft hole, and an outer movable sleeve arranged between the inner movable sleeve and the fixed sleeve shaft hole.

[0018] Preferably, the graphite mold in step (8) is a hollow cylinder, and plugs are respectively provided at the hollow ends of the cylinder.

[0019] The present invention has the following advantages and beneficial effects:

[0020] The present invention is prepared by the above technical scheme: the outer layer is a porous layer (porosity between 55 and 65%), the inner core is a porous layer (porosity between 60 and 70%), and the middle is a dense layer of bone-like structure multifunctional medical titanium alloy, which has high compressive strength (≥610MPa), low elastic modulus (≤12GPa), the pore size of the macropore is 100 to 600μm, the pore size of the micropore is less than 50μm, and the distribution is uniform. The porous structure of the outer layer is conducive to promoting the growth of bone tissue, the dense layer in the middle can play a bearing and supporting role, the porous structure of the inner core can promote the transportation of nutrients and the formation of new blood vessels, and the porous structures of the inner core and the outer layer can also play a role in stress release and buffering motion load, which can improve the bone integration effect of the implant. At the same time, the pre-alloyed Ti6Al4V5Cu and Ti6Al4V alloy powder raw materials are used to achieve precise control of elements and effectively avoid the problem of chemical composition segregation; and because the Ti6Al4V5Cu alloy has excellent antibacterial properties, it can effectively inhibit bacterial infection after implantation. The present invention has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a morphology diagram of the pre-alloyed spherical Ti6Al4V5Cu metal powder of the present invention;

[0022] Figure 2 This is a morphology diagram of the pre-alloyed angular Ti6Al4V metal powder of the present invention;

[0023] Figure 3 This is a schematic diagram of the stainless steel mold structure and pre-pressing process of the present invention;

[0024] Figure 4 This is an optical microscopic morphology of the interface between the inner core porous layer and the dense layer of the bone-like structure multifunctional medical titanium alloy prepared in Example 1 of the present invention;

[0025] Figure 5 This is an optical microscopic morphology of the interface between the outer porous layer and the dense layer of the bone-like structure multifunctional medical titanium alloy prepared in Example 1 of the present invention;

[0026] Figure 6 The compressive strength-elastic modulus diagram of the bone-like multifunctional medical titanium alloy prepared in Examples 1, 2, and 3 of the present invention;

[0027] Figure 7 This is a compressive strength-elastic modulus diagram of the bone-like structure multifunctional medical titanium alloy prepared in Examples 1, 4, and 5 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0029] The stainless steel mold used in the embodiment of the present invention includes a fixed sleeve 1, a cushion block 2 arranged at the bottom of the axial hole of the fixed sleeve 1, an inner movable sleeve 3 movably arranged on the cushion block 2, a core rod 4 movably arranged in the axial hole of the inner movable sleeve 3, and an outer movable sleeve 5 arranged between the inner movable sleeve 3 and the axial hole of the fixed sleeve 1.

[0030] The graphite mold used in the embodiment of the present invention is a hollow cylinder, and plugs are respectively arranged at the hollow ends of the cylinder.

[0031] Example 1

[0032] A method for preparing a bone-like multifunctional medical titanium alloy comprises the following steps:

[0033] (1) Pre-alloyed Ti6Al4V5Cu spherical metal powder with a particle size of 10 μm and Ti6Al4V angular metal powder with a particle size of 40 μm are used as raw materials; wherein:

[0034] The chemical composition of the Ti6Al4V5Cu metal powder is: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;

[0035] The chemical composition of the Ti6Al4V metal powder is: Al: 5.99wt.%, V: 4.20wt.%, Fe: 0.037wt.%, C: 0.026wt.%, N: 0.012wt.%, H: 0.0025wt.%, O: 0.058wt.%, and the balance is Ti;

[0036] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein: the mass fraction of the NH4HCO3 powder is 30%; the purity of the NH4HCO3 powder is analytical purity, and the particle size is 300 μm;

[0037] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 40°C, cooling them to room temperature, and obtaining a mixture II for standby use; wherein the ratio of the added amount of Ti6Al4V5Cu to the liquid paraffin is 5.17 g / ml;

[0038] (4) adding the Ti6Al4V5Cu metal powder used as the core porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 45%;

[0039] (5) Vaseline is evenly coated on the inner wall of the axial hole of the fixed sleeve 1 of the stainless steel mold, and then the cushion block 2 is placed at the bottom of the axial hole, and then the inner movable sleeve 3 and the core rod 4 in the axial hole are inserted onto the cushion block 2, and then the mixture I of step (2) is filled between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the outer movable sleeve 5 is inserted between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the mixture I is compacted to form a hollow outer layer material column A1; then the inner movable sleeve 3 is pulled out, and the mixture II of step (3) is filled between the outer wall of the core rod 4 and the hollow column A1 and the axial hole of the outer movable sleeve 5, and the inner movable sleeve 3 is inserted to compact the mixture II to form a hollow middle material column A2; then the core rod 4 is pulled out, and the mixture III of step (4) is filled into the empty position of the core rod 4, and the core rod 4 is inserted to compact the mixture III to form a core material column A3;

[0040] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, applying pressure to 50 kN at a speed of 1 kN / S, maintaining the pressure for 30 min, and removing the mold to obtain a green billet;

[0041] (7) placing the green body of step (6) into a tubular furnace, degreasing the green body in an atmosphere of argon gas with a purity of 99.99% and a vacuum degree of 10 Pa in the furnace, heating the body to 250° C. at a heating rate of 5° C. / min during the degreasing process, then keeping the temperature for 240 min, cooling the body to room temperature at a cooling rate of 5° C. / min, opening the furnace and taking the green body out to obtain a degreased green body for standby use;

[0042] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 100°C / min, and then increased to 900°C at a heating rate of 100°C / min, and then increased to 1150°C at a heating rate of 50°C / min, and kept warm for 10 minutes. Thereafter, under the condition of a vacuum degree of 6 Pa in the furnace, the temperature is cooled to 150°C at a cooling rate of 90°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0043] Example 2

[0044] A method for preparing a bone-like multifunctional medical titanium alloy comprises the following steps:

[0045] (1) Pre-alloyed Ti6Al4V5Cu spherical metal powder with a particle size of 15 μm and Ti6Al4V angular metal powder with a particle size of 45 μm are used as raw materials; wherein:

[0046] The chemical composition of the Ti6Al4V5Cu metal powder is: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;

[0047] The chemical composition of the Ti6Al4V metal powder is: Al: 5.99wt.%, V: 4.20wt.%, Fe: 0.037wt.%, C: 0.026wt.%, N: 0.012wt.%, H: 0.0025wt.%, O: 0.058wt.%, and the balance is Ti;

[0048] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein: the mass fraction of the NH4HCO3 powder is 35%; the purity of the NH4HCO3 powder is analytical purity, and the particle size is 400 μm;

[0049] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 30°C, cooling them to room temperature, and obtaining a mixture II for standby use; wherein the ratio of the added amount of Ti6Al4V5Cu to the liquid paraffin is 5.58 g / ml;

[0050] (4) adding the Ti6Al4V5Cu metal powder used as the middle and outer porous layers in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 50%;

[0051] (5) The structure of the stainless steel mold used is the same as that of Example 1. Vaseline is evenly coated on the inner wall of the axial hole of the fixed sleeve 1 of the stainless steel mold, and then the cushion block 2 is placed at the bottom of the axial hole, and then the inner movable sleeve 3 and the core rod 4 in the axial hole are inserted onto the cushion block 2. Then, the mixture I of step (2) is filled between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the outer movable sleeve 5 is inserted between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1. After the mixture I is compacted, a hollow outer layer material column A1 is formed; then the inner movable sleeve 3 is pulled out, and the mixture II of step (3) is filled between the outer wall of the core rod 4 and the hollow column A1 and the axial hole of the outer movable sleeve 5, and the inner movable sleeve 3 is inserted to compact the mixture II to form a hollow middle material column A2; then the core rod 4 is pulled out, and the mixture III of step (4) is filled into the empty position of the core rod 4, and the core rod 4 is inserted to compact the mixture III to form a core material column A3;

[0052] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 40 kN at a speed of 3 kN / S, maintaining the pressure for 20 min, and removing the mold to obtain a pre-pressed blank;

[0053] (7) placing the pre-pressed blank of step (6) into a tubular furnace, degreasing the blank in a furnace with a vacuum degree of 15 Pa and a continuous flow of argon gas with a purity of 99.99%. During the degreasing process, the temperature is increased to 230° C. at a heating rate of 5° C. / min, then kept at this temperature for 240 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a degreased blank for standby use;

[0054] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 5 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 90°C / min, and then increased to 900°C at a heating rate of 110°C / min, and then increased to 1150°C at a heating rate of 45°C / min, and kept warm for 10 minutes. Thereafter, under the condition of a vacuum degree of 5 Pa in the furnace, the temperature is cooled to 200°C at a cooling rate of 85°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0055] Example 3

[0056] A method for preparing a bone-like multifunctional medical titanium alloy comprises the following steps:

[0057] (1) Pre-alloyed Ti6Al4V5Cu spherical metal powder with a particle size of 20 μm and Ti6Al4V angular metal powder with a particle size of 50 μm are used as raw materials; wherein:

[0058] The chemical composition of the Ti6Al4V5Cu metal powder is: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;

[0059] The chemical composition of the Ti6Al4V metal powder is: Al: 5.99wt.%, V: 4.20wt.%, Fe: 0.037wt.%, C: 0.026wt.%, N: 0.012wt.%, H: 0.0025wt.%, O: 0.058wt.%, and the balance is Ti;

[0060] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein: the mass fraction of the NH4HCO3 powder is 40%; the purity of the NH4HCO3 powder is analytical purity, and the particle size is 400 μm;

[0061] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 35°C, cooling them to room temperature, and obtaining a mixture II for standby use; wherein the ratio of the added amount of Ti6Al4V5Cu to the liquid paraffin is 4.96 g / ml;

[0062] (4) adding the Ti6Al4V5Cu metal powder used as the middle and outer porous layers in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 55%;

[0063] (5) The structure of the stainless steel mold used is the same as that of Example 1. Vaseline is evenly coated on the inner wall of the axial hole of the fixed sleeve 1 of the stainless steel mold, and then the cushion block 2 is placed at the bottom of the axial hole, and then the inner movable sleeve 3 and the core rod 4 in the axial hole are inserted onto the cushion block 2. Then, the mixture I of step (2) is filled between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the outer movable sleeve 5 is inserted between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1. After the mixture I is compacted, a hollow outer layer material column A1 is formed; then the inner movable sleeve 3 is pulled out, and the mixture II of step (3) is filled between the outer wall of the core rod 4 and the hollow column A1 and the axial hole of the outer movable sleeve 5, and the inner movable sleeve 3 is inserted to compact the mixture II to form a hollow middle material column A2; then the core rod 4 is pulled out, and the mixture III of step (4) is filled into the empty position of the core rod 4, and the core rod 4 is inserted to compact the mixture III to form a core material column A3;

[0064] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 40 kN at a speed of 2 kN / S, maintaining the pressure for 35 min, and removing the mold to obtain a pre-pressed blank;

[0065] (7) placing the pre-pressed blank of step (6) into a tubular furnace, degreasing the blank in a furnace with a vacuum degree of 20 Pa and continuously introducing an argon atmosphere with a purity of 99.99%. During the degreasing process, the temperature is increased to 240° C. at a heating rate of 5° C. / min, then kept at this temperature for 220 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a degreased blank for standby use;

[0066] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 95°C / min, and then increased to 900°C at a heating rate of 105°C / min, and then increased to 1150°C at a heating rate of 50°C / min, and kept warm for 10 minutes. Thereafter, under the condition of a vacuum degree of 6 Pa in the furnace, the temperature is cooled to 200°C at a cooling rate of 80°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0067] Example 4

[0068] A method for preparing a bone-like multifunctional medical titanium alloy comprises the following steps:

[0069] (1) Pre-alloyed Ti6Al4V5Cu spherical metal powder with a particle size of 10 μm and Ti6Al4V angular metal powder with a particle size of 40 μm are used as raw materials; wherein:

[0070] The chemical composition of the Ti6Al4V5Cu metal powder is: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;

[0071] The chemical composition of the Ti6Al4V metal powder is: Al: 5.99wt.%, V: 4.20wt.%, Fe: 0.037wt.%, C: 0.026wt.%, N: 0.012wt.%, H: 0.0025wt.%, O: 0.058wt.%, and the balance is Ti;

[0072] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein: the mass fraction of the NH4HCO3 powder is 30%; the purity of the NH4HCO3 powder is analytical purity, and the particle size is 300 μm;

[0073] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 33°C, cooling them to room temperature, and obtaining a mixture II for standby use; wherein the ratio of the added amount of Ti6Al4V5Cu to the liquid paraffin is 5.26 g / ml;

[0074] (4) adding the Ti6Al4V5Cu metal powder used as the middle and outer porous layers in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 48%;

[0075] (5) The structure of the stainless steel mold used is the same as that of Example 1. Vaseline is evenly coated on the inner wall of the axial hole of the fixed sleeve 1 of the stainless steel mold, and then the cushion block 2 is placed at the bottom of the axial hole, and then the inner movable sleeve 3 and the core rod 4 in the axial hole are inserted onto the cushion block 2. Then, the mixture I of step (2) is filled between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the outer movable sleeve 5 is inserted between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1. After the mixture I is compacted, a hollow outer layer material column A1 is formed; then the inner movable sleeve 3 is pulled out, and the mixture II of step (3) is filled between the outer wall of the core rod 4 and the hollow column A1 and the axial hole of the outer movable sleeve 5, and the inner movable sleeve 3 is inserted to compact the mixture II to form a hollow middle material column A2; then the core rod 4 is pulled out, and the mixture III of step (4) is filled into the empty position of the core rod 4, and the core rod 4 is inserted to compact the mixture III to form a core material column A3;

[0076] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 40 kN at a speed of 3 kN / S, maintaining the pressure for 28 min, and removing the mold to obtain a pre-pressed blank;

[0077] (7) placing the pre-pressed blank of step (6) into a tubular furnace, degreasing the blank in a furnace with a vacuum degree of 25 Pa and a continuous flow of argon gas with a purity of 99.99%. During the degreasing process, the temperature is increased to 245° C. at a heating rate of 5° C. / min, then kept at this temperature for 225 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a degreased blank for standby use;

[0078] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 100°C / min, and then increased to 900°C at a heating rate of 100°C / min, and then increased to 1100°C at a heating rate of 50°C / min, and kept warm for 10 minutes. Thereafter, under the condition of a vacuum degree of 6 Pa in the furnace, the temperature is cooled to 250°C at a cooling rate of 90°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0079] Example 5

[0080] A method for preparing a bone-like multifunctional medical titanium alloy comprises the following steps:

[0081] (1) Pre-alloyed Ti6Al4V5Cu spherical metal powder with a particle size of 15 μm and Ti6Al4V angular metal powder with a particle size of 45 μm are used as raw materials; wherein:

[0082] The chemical composition of the Ti6Al4V5Cu metal powder is: Al: 6.08wt.%, V: 3.98wt.%, Cu: 5.01wt.%, Fe: 0.028wt.%, C: 0.011wt.%, N: 0.007wt.%, H: 0.0015wt.%, O: 0.067wt.%, and the balance is Ti;

[0083] The chemical composition of the Ti6Al4V metal powder is: Al: 5.99wt.%, V: 4.20wt.%, Fe: 0.037wt.%, C: 0.026wt.%, N: 0.012wt.%, H: 0.0025wt.%, O: 0.058wt.%, and the balance is Ti;

[0084] (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein: the mass fraction of the NH4HCO3 powder is 30%; the purity of the NH4HCO3 powder is analytical purity, and the particle size is 500 μm;

[0085] (3) adding the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mixing them at 38°C, cooling them to room temperature, and obtaining a mixture II for standby use; wherein the ratio of the added amount of Ti6Al4V5Cu to the liquid paraffin is 4.99 g / ml;

[0086] (4) adding the Ti6Al4V5Cu metal powder used as the middle and outer porous layers in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 51%;

[0087] (5) The structure of the stainless steel mold used is the same as that of Example 1. Vaseline is evenly coated on the inner wall of the axial hole of the fixed sleeve 1 of the stainless steel mold, and then the cushion block 2 is placed at the bottom of the axial hole, and then the inner movable sleeve 3 and the core rod 4 in the axial hole are inserted onto the cushion block 2. Then, the mixture I of step (2) is filled between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1, and the outer movable sleeve 5 is inserted between the outer wall of the inner movable sleeve 3 and the axial hole of the fixed sleeve 1. After the mixture I is compacted, a hollow outer layer material column A1 is formed; then the inner movable sleeve 3 is pulled out, and the mixture II of step (3) is filled between the outer wall of the core rod 4 and the hollow column A1 and the axial hole of the outer movable sleeve 5, and the inner movable sleeve 3 is inserted to compact the mixture II to form a hollow middle material column A2; then the core rod 4 is pulled out, and the mixture III of step (4) is filled into the empty position of the core rod 4, and the core rod 4 is inserted to compact the mixture III to form a core material column A3;

[0088] (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 45 kN at a speed of 1 kN / S, maintaining the pressure for 32 min, and removing the mold to obtain a pre-pressed blank;

[0089] (7) placing the pre-pressed blank of step (6) into a tubular furnace, degreasing the blank in a furnace with a vacuum degree of 22 Pa and continuously introducing an argon atmosphere with a purity of 99.99%. During the degreasing process, the temperature is increased to 245° C. at a heating rate of 5° C. / min, then kept at that temperature for 235 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a degreased blank for standby use;

[0090] (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 100°C / min, and then increased to 900°C at a heating rate of 100°C / min, and then increased to 1200°C at a heating rate of 50°C / min, and kept warm for 10 minutes. Thereafter, under the condition of a vacuum degree of 6 Pa in the furnace, the temperature is cooled to 250°C at a cooling rate of 80°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

[0091] The porosity of the outer layer and the density of the middle layer of the bone-like multifunctional medical titanium alloy prepared in the present invention were tested by the Archimedean drainage method. To ensure that the results were statistically significant, the average values ​​were obtained after multiple tests. The test results are shown in Tables 1 and 2.

[0092] Table 1 Effect of pore-forming agent mass fraction on the porosity of the outer layer of bone-like multifunctional medical titanium alloy

[0093]

[0094]

[0095] Table 2 Effect of sintering temperature on the density of the intermediate layer of bone-like multifunctional medical titanium alloy

[0096] Sintering temperature(℃) 1100 1150 1200 Density(%) 92.06 92.74 93.17

[0097] The dimensions of the pre-pressed green body and the sintered sample were measured with a vernier caliper, and the shrinkage of the sample was calculated. The longitudinal shrinkage of the bone-structure multifunctional medical titanium alloy was 14.3%, and the transverse shrinkage was 9.6%.

[0098] The mechanical properties (compressive strength, elastic modulus) of the material were tested in a mechanical testing machine according to GB / T 31930-2015 standard. To ensure that the results are statistically significant, the average value was taken from multiple tests. Figure 6 , 7 The test results meet the requirements of compressive strength and elastic modulus for implantation in the human body.

[0099] The surface of the multifunctional medical titanium alloy material with bone structure was observed and analyzed using an optical microscope. Figure 4 , 5 This is a surface optical microscope image of the sintered sample. It can be seen from the image that the interface of the bone-like multifunctional medical titanium alloy material is well bonded, the porosity of the outer porous layer is between 55% and 65%, and the porosity of the core porous layer is between 60% and 70%. The pore size of the macropores is between 100 and 600 μm, and the pore size of the micropores is less than 50 μm and is evenly distributed.

[0100] In summary, the bone-like structure multifunctional medical titanium alloy prepared by the above technical scheme in the present invention has an outer porous structure that is conducive to promoting the ingrowth of bone tissue, a middle dense layer that can play a bearing and supporting role, an internal porous structure that can promote nutrient delivery and new blood vessel formation, and internal and external porous structures that can also release stress and buffer motion loads, thereby improving the bone integration effect of the implant.

Claims

1. A method for preparing a bone-like multifunctional medical titanium alloy, characterized in that The following steps are included: (1) Using pre-alloyed spherical Ti6Al4V5Cu alloy powder with a particle size of 10-20 μm and angular Ti6Al4V alloy powder with a particle size of 40-50 μm as raw materials; (2) adding the Ti6Al4V metal powder used as the outer porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture I for standby use, wherein the mass fraction of the NH4HCO3 powder is 30-40%; (3) Add the Ti6Al4V5Cu metal powder used as the base layer in step (1) to the liquid paraffin used as the binder, mix them at 30-40°C, and cool them to room temperature to obtain a mixture II for standby use; wherein the addition amount of Ti6Al4V5Cu and liquid paraffin is 4.86-5.67 g / ml; (4) adding the Ti6Al4V5Cu metal powder used as the core porous layer in step (1) to the NH4HCO3 powder used as the pore-forming agent, mixing them evenly to obtain a mixture III for standby use; wherein the mass fraction of the NH4HCO3 powder is 45-60%; (5) Vaseline is evenly coated on the inner wall of the stainless steel mold, and then the mixture I of step (2) is first filled into the stainless steel mold and pressed into a hollow cylinder. Then the mixture II of step (3) is filled between the cylinder and the core, and finally the mixture III of step (4) is filled into the core of the cylinder; and the mixture is hammered and compacted while being filled; (6) placing the stainless steel mold containing the compacted material in step (5) on a press, pressurizing to 40-60 kN at a speed of 1-3 kN / S, maintaining the pressure for 20-40 min, and removing the mold to obtain a green billet; (7) placing the green body of step (6) into a tubular furnace, debinding the green body in a furnace with a vacuum degree of 10-25 Pa and continuously introducing an argon atmosphere with a purity of 99.99%. During the debinding process, the temperature is increased to 230-250° C. at a heating rate of 5° C. / min, then kept at this temperature for 220-240 min, cooled to room temperature at a cooling rate of 5° C. / min, the furnace is opened and taken out to obtain a debinded green body for standby use; (8) The degreased blank of step (7) is placed in a graphite mold, and placed in a spark plasma sintering furnace. Under the condition of a vacuum degree of 4-6 Pa in the sintering furnace, the temperature is increased to 600°C at a heating rate of 90-100°C / min, and then increased to 900°C at a heating rate of 100-110°C / min, and then increased to 1100-1200°C at a heating rate of 45-50°C / min, and kept warm for 5-10 minutes. Thereafter, under the condition of a vacuum degree of 4-6 Pa in the furnace, the temperature is cooled to 150-250°C at a cooling rate of 70-90°C / min, and then cooled to room temperature with the furnace. The furnace is opened, the mold is taken out, and the mold is removed to obtain: a bone-like structure multifunctional medical titanium alloy with a porous outer layer, a porous inner core, and a dense middle layer.

2. The method for preparing the bone-like multifunctional medical titanium alloy according to claim 1, characterized in that: The chemical composition of the Ti6Al4V5Cu metal powder in step (1) is: Al: 5.50-6.50 wt.%, V: 3.50-4.50 wt.%, Cu: 4.5-6.0 wt.%, Fe: ≤0.25 wt.%, C: ≤0.08 wt.%, N: ≤0.03 wt.%, H: ≤0.008 wt.%, O: ≤0.13 wt.%, and the balance is Ti; The chemical composition of the Ti6Al4V metal powder is: Al: 5.50-6.75wt.%, V: 3.50-4.50 wt.%, Fe: ≤0.30wt.%, C: ≤0.08 wt.%, N: ≤0.05wt.%, H: ≤0.015wt.%, O: ≤0.20 wt.%, and the balance is Ti.

3. The method for preparing the bone-like multifunctional medical titanium alloy according to claim 1, characterized in that: The Ti6Al4V5Cu metal powder in step (1) is prepared by electrode induction melting and inert gas atomization; the Ti6Al4V metal powder is prepared by ball milling.

4. The method for preparing the bone-like multifunctional medical titanium alloy according to claim 1, characterized in that: The purity of the NH4HCO3 powder in steps (2) and (4) is analytical purity, and the particle size is 300-500 μm.

5. The method for preparing the bone-like multifunctional medical titanium alloy according to claim 1, characterized in that: The stainless steel mold in step (5) includes a fixed sleeve, a cushion block arranged at the bottom of the fixed sleeve shaft hole, an inner movable sleeve movably arranged on the cushion block, a core rod movably arranged in the inner movable sleeve shaft hole, and an outer movable sleeve arranged between the inner movable sleeve and the fixed sleeve shaft hole.

6. The method for preparing the bone-like multifunctional medical titanium alloy according to claim 1, characterized in that: The graphite mold in step (8) is a hollow cylinder, and plugs are respectively arranged at the two hollow ends of the cylinder.